Spain and Mexico: Parallelism, Confluences and Confrontations (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
First of all, we are going to explain the parallelisms around the “agricultural issue” with the intention of showing how this problem has become deeply embedded in both countries and has brought them similar structural problems. Secondly, we will attempt to explain the same problem around the republican exile in Mexico, focusing in the institutional dimension of it. Thirdly, accordingly to Adolfo Sánchez Vázquez concept of exile and his critique against Gaos’s the concept of “transterrado”1, we are going to analyse the way in which the philosophical and historical problems of the relationships between Spain and Latin America has been undertaken.